Green synthesis of silver/zinc oxide plasmonic nanocomposites using Moringa oleifera: A dual-function strategy for photocatalysis and dye-sensitized solar cell performance - Kandasamy Muthusamy; Velu Duraisamy; Jayant Giri; Prem Gunnasegaran; Ahmad Husain; V. Vicki Wanatasappan; Mohammad Kanan (Journal of Science: Advanced Materials and Devices)
Chemical methods are the primary techniques for large-scale nanomaterial synthesis, offering environmental and energy benefits; however, these methods negatively impact on the environment. To circumvent this, an eco-friendly approach produces nanoparticles that effectively degrade dyes under light exposure, showing promise in dye-sensitized solar cells (DSSCs). A sustainable green synthesis of plasmonic silver nanoparticles decorated zinc nanocomposite (Ag@ZnO PNC) by Moringa oleifera leaf extract as both reducing and capping agents by a simple solution method. Prepared plasmonic material was characterized using advanced instrumentation techniques. The photocatalytic performance of green synthesized plasmonic Ag@ZnO PNC was tested for the degradation of methylene blue under direct sunlight irradiation. The plasmonic Ag@ZnO PNC improved the photocatalytic performance by 99.33 % because of a higher amount of ●OH production verified by the terephthalic acid experiment. Likewise, a dye-sensitized solar cell (DSSC) with Ag@ZnO NC photoanode exhibited a higher energy conversion of efficiency (PCE) of 1.76 %, which is ∼33 % higher over the PCE of DSSC with pure ZnO (1.18 %), which is attributed to the incorporation of Ag, which acts as electron sink and offered visible light extensions.